Streptococcus pyogenes meningitis and endocarditis in a patient with prosthetic mitral valve. Issue 3 (September 2017) - Wang, Stephani C.; Torosoff, Mikhail T.; Smith, Raymond P.; Coates, Andrew D.
Abstract: Streptococcus pyogenes is commonly found in cutaneous and pharyngeal infections, but rarely causes meningitis and endocarditis. We report a 77-year-old male with history of prosthetic mitral valve, presenting with meningitis and endocarditis secondary to S. pyogenes . We aim to raise awareness among clinicians of rare infectious etiology as the cause of endocarditis and meningitis, and importance of prompt diagnosis in ensuring success of medical treatment and long-term survival. <Learning objective: Main learning objectives are: (1) Rare sources of infection should be considered in setting of endocarditis and meningitis. (2) In high-risk patients, transesophageal echocardiogram is indicated although initial transthoracic echocardiogram may not show classic vegetation.>